1995
DOI: 10.1029/94gl03298
|View full text |Cite
|
Sign up to set email alerts
|

Is there truly a “hard” rock site in the Valley of Mexico?

Abstract: To understand the cause of observed amplification of seismic waves even at hill‐zone sites in the Valley of Mexico, digital accelerographs have been installed at three especially chosen sites. Two of these sites, MADI and TEXC, located on hard Pleistocene lava (a few meters in thickness) overlying Oligocene andesites, were expected to be free of site effects. Analysis of the data recorded by these and other accelerographs during three moderate, shallow subduction zone events, however, shows significant amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 4 publications
5
42
0
4
Order By: Relevance
“…This result agrees with Singh et al [1995], who reported a maximum amplification of 10 at frequencies between 0.2 and 0.4 Hz for CUIG. For TUIG, high amplification is obtained at high frequencies, which is expected since the station is located on sediments.…”
Section: Discussionsupporting
confidence: 82%
“…This result agrees with Singh et al [1995], who reported a maximum amplification of 10 at frequencies between 0.2 and 0.4 Hz for CUIG. For TUIG, high amplification is obtained at high frequencies, which is expected since the station is located on sediments.…”
Section: Discussionsupporting
confidence: 82%
“…It may be argued that the ground motion at frequencies above I Hz is of no consequence to seismic risk in Mexico City since the damage results from extraordinary amplification of seismic waves in the soft subsoil of the lake-bed zone of city at the dominant period of the site which is around 2 sec [Singh et at., 1988[Singh et at., , 1995. There is, however, reason to believe that large intraplate earthquakes, which occur in the subducted Cocos plate, can cause damage to low-rise structures which are sensitive to high-frequency ground motion.…”
Section: Spectral Ratiosmentioning
confidence: 99%
“…La figura muestra que la forma del EPU para la estación de CU es significativamente diferente que para los sitios cercanos a la región de la costa del Pacífico Mexicano, y que las magnitudes del EPU son comparables a aquéllas para la zona costera solamente para estructuras con periodos de vibración largos. Cabe mencionar que Singh et al (1995) señalaron las diferencias de los efectos sísmicos en el valle de México y en la zona de la costa del Pacífico para algunos sismos históricos individuales.…”
Section: Peligro Sísmico Y Mapas De Contornounclassified